Private Company Law reform in europe: the race for flexibility - Teichmann, Christoph (Cizur Menor, Navarra Aranzadi, 2015)
The legal model of closely held companies (essentially, limited liability companies) prior to 1990 has been revised, to a greater or lesser extent, in practically all the legislations of the European Union Member States. However, contrary to what one might think, after the European Union Court of Justice?s decisions in the Centros, Inspire Art and Überserring cases, the outcome has not been fully consistent throughout all such legislations. This book offers comprehensive insight into the different legislative developments in the most significant legislations of the European Union, with the participation of renowned specialists from Belgium, Denmark, France, Germany, Ireland, Italy, Lithuania, Luxembourg, Netherlands, Poland, Portugal, Spain and United Kingdom. Los modelos legales de sociedades de capital cerradas (esencialmente la sociedad de responsabilidad limitada) anteriores a 1990 han sido revisados, con mayor o menor intensidad, en casi todas las legislaciones de los Estados de la Unión Europea. Sin embargo, en contra de lo que se podía pensar, tras la jurisprudencia del Tribunal de Justicia de la Unión Europea en los conocidos casos Centros, Inspire Art y Überserring, los resultados legislativos no han sido plenamente homogéneos. El presente libro ofrece una visión en profundidad de esos distintos procesos de evolución legislativa en las legislaciones más significativas de la Unión Europea, a través de la participación de reconocidos especialistas de Belgium, Denmark, France, Germany, Holland, Ireland, Italy, Lithuania, Luxembourg, Poland, Portugal, Spain and United Kingdom.
Keywords: Derecho internacional